Francis L. Moore letter to Thomas H. Kent regarding bird sightings, May 30, 1980 - Moore, Francis L.et al (1980)
Field notes contributed by Francis L. Moore in a letter to Thomas H. Kent, May 30, 1980 with observers Robert K. Myers, Russel Hays, Joseph P. Schaufenbuel and others. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1980. Epson - sheet feed/flatbed